(untitled) (Trabalho & Educação, 2018)
The present article addresses a particular aspect of the struggle for the conquest of hegemony in Antonio Gramsci (1891-1937), that is, the cultural aspect. However, it does not treat it as an isolated element, because it seeks to apprehend it in its organic relation in the whole of social life. In this sense, it aims to demonstrate that the cultural aspect, precisely because of its organic character, is not merely ancillary but constitutive of the Gramscian concept of hegemony and fundamental in the formation of the new “collective man”, the foundation of the future social order. Essential to this reflection is therefore the idea of organicity, through which Gramsci approaches culture, politics and all aspects of social life, seeking to distinguish arbitrary and transient constructions from those of enduring. We can say that it is in the idea of organicity that everything is found and acquires meaning. ___ O presente artigo aborda um aspecto particular da luta pela conquista da hegemonia em Antonio Gramsci (1891-1937), ou seja, o aspecto cultural. No entanto, não o trata como um elemento isolado, porque procura apreendê-lo em sua relação orgânica no conjunto da vida social. Nesse sentido, tem por objetivo demonstrar que o aspecto cultural, exatamente pelo seu caráter orgânico, não é meramente acessório, mas constitutivo do conceito gramsciano de hegemonia e fundamental na formação do novo “homem coletivo”, o alicerce da futura ordem social. Essencial para essa reflexão é, portanto, a ideia de organicidade, por meio da qual Gramsci aborda a cultura, a política e todos os aspectos da vida social, procurando distinguir as construções arbitrárias e passageiras daquelas duradouras. Podemos dizer que é na ideia de organicidade que tudo se encontra e adquire sentido.